Inflow/Outflow: A Web Of Contrasting Realities And Aspirations In Shapeshifting Urban Accra - Addo-Atuah, Kweku (MAJ - Malaysia Architectural Journal, 2025)
Accra, Ghana is a city in constant flux. It finds itself entangled on several fronts, caught in the push-and-pull of divergent national and international aspirations, optics, and realities. Amidst the glitz and glamour of global media coverage touting it as a growing cultural force due to its artistic and tourism ecosystem, the spotlight shines unfavourably on the Odaw River-Korle Lagoon catchment. Originally a wetland that now serves as Accra’s principal drainage system, Odaw-Korle is at once croaking from the informal communities formed along its bank and the decades-long domestic and international e-waste dumping volumes on its surface areas. Not only does the compromised Odaw-Korle threaten Accra’s full-service drainage capacity, but it also leaves Accra vulnerable to a multitude of environmentally-driven public health devastations. The paper contextualizes the Odaw-Korle catchment, from its historical evolution, its relationship to past and current governmental efforts to tackle this challenge, and utilizes research papers and scholarly research studies to gain a broad-spectrum and multi-scale understanding of the issues and forces at play. Operating mainly as a speculative study driven by findings expressed or alluded to from the presented research methodology, the paper will explore concepts of waste economies, socioecological infrastructural systems and adaptive urbanism strategies. Through this, the paper builds upon past literature, but goes further through a landscape urbanism praxis to reimagine an Odaw-Korle Catchment and Accra that is resilient and supports the agency and balanced livability of its residents across a wide spectrum of economic classes.